Russian Approach to Soft Power Promotion: Conceptual Approaches in Foreign Policy - Y. Nikitina (Vestnik MGIMO-Universiteta)
Foreign policy is one of the instruments of promoting soft power of a state. According to Joseph Nye, civil society is the main source of a state's international attractiveness. The article analyses how Russian official foreign policy documents present interaction between the state and civil society in order to promote Russian soft power. At the present stage Russian civil society is perceived by state structures as an instrument and not a source of soft power. The article also analyses political values and models of developments as elements of soft power as they are presented in official documents. Russia has a coherent normative model of regional development for the post-Soviet space. For the global level Russia formulates rules of behavior that it would like to see at the international arena, but Russia does not formulate how Russian or regional post-Soviet models of development can contribute to world development.